ANALISIS IMPELMENTASI PENGEMBANGAN POS PEMBINAAN TERPADU (POSBINDU) PENYAKIT TIDAK MENULAR KE POSYANDU TERINTEGRASI DI KABUPATEN LEBAK - Ahmad, Ahmad; Suhartini, Suhartini; Purbianto, Purbianto; Bakhtiar, Bakhtiar (Jurnal Medikes (Media Informasi Kesehatan), 2024)
Abstract A public health center as a health facility not only provides services inside the building but also provides health services to the community outside the building. Some of the health services outside the building included Posyandu for Mother and Balita, for teenagers, and integrated building posts for communities aged 15 and over, as an effort to control the increase in the incidence of pain and deaths from non-communicable diseases (PTM). Currently, the government has a policy to develop a Posyandu Prima program that integrates some of the Puskesmas services outside the building into an integrated Posyandu program. The development policy of this primary program requires support from the human resources department of health as an implementer, means of implementation, budget, monitoring and evaluation, and reporting as part of program accountability. The research is aimed at obtaining an overview of the implementation of the Integrated Disease Integrated Construction Post program to integrate Posyandu in the district. Cross-sectional research design. Data is collected through FGD with PTM Puskesmas program administrators, caders, post-mortem missionaries, the head of the Puskesmas, and direct observation of the implementation of primary Posyandu in society. The results of the research show that Lebak district has an integrated one-posyandu program in each village that serves the target population of pregnant mothers, babies, infants, adolescents, and the elderly, but its implementation has not gone well. Meanwhile, the Posyandu activities that serve mother and child health, as well as the PTM post-mortem, are still ongoing. Officer and community access to the relatively remote, integrated Posyandu location, as well as limited support of the Posyandu location. Understanding of the framework of integrated health management Posyandu still lacks, especially in carrying out the reporting of PTM post-mortem activities through “ASIK applications (Aplikasi Sehat Indonesiaku)”. The budget support for preparing the Prasarana Posyandu Prima (integrated) facilities in each village is still low. The Cabinet Health Service needs to optimize the Puskesmas Health Force and improve the education and socialization of the Posyandu Prima (integrated) program for the Health Force in the Puskesmas and the Health Care Caders in the Community, as well as improving the Posyandu Prima (integrated) facilities.